The pedagogical content knowledge development of prospective teachers through an experiential task - KURT TİFTİK, GÖKÇE; KAŞLIOĞLU, ÖZLEM (ELSEVIER SCIENCE BV, 2010)
Pedagogical content knowledge (PCK) forms a knowledge base for teachers, guiding their decisions and actions in classrooms. The value of PCK has been emphasized since late 1980s, yet, still not much is known about the process of PCK development among prospective teachers. The present study aims to investigate the PCK development of Turkish prospective teachers through the process of an experiential task. Data were collected from 18 participants through focus group interviews and narratives, and analyzed by means of qualitative methods. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Pedagogical content knowledge; pre-service teacher education